Global lifetime and 12-month prevalence of suicidal behavior, deliberate self-harm and non-suicidal self-injury in children and adolescents between 1989 and 2018: A meta-analysis - Lim, K.-S. (MDPI AG, 2022)
10.3390/ijerph16224581